Exploring the determinants of entitlement mentality among Generation Y in two tertiary institutions in Johannesburg, South Africa - Nkomo, Emmanuel (My University, 2017)
For the past two years, South Africa has been gripped by a spate of demonstrations by university students demanding free university education. These demonstrations have been violent, and mediation efforts have not succeeded in yielding long-term results. According to the theory of rising expectations, in an economy that is improving and where the people are not oppressed, their expectations often outstrip the pace of actual change (Gale, 2008). When there is a mismatch between what people expect and what they actually get, theory suggests that rising expectations lead to civil unrest as demands for improvement continue to grow. It is the contention of this thesis that the theory of rising expectations is associated with the behaviour of the university students as they make demands for free education, better employment opportunities and more accountability from the government. Also associated with the behaviour of these university students in South Africa is generational cohort theory, which predicts that certain significant national and global events have a long-lasting impact on value systems of individual groups and social orders resulting in the formation of new generational cohorts (Smolla & Sutton, 2002). These individuals then share enduring distinctive sets of values, beliefs, and behaviours (Strauss & Howe, 2000). Furthermore, research suggests that Generation Y are materialistic, which is the value individuals place on possessions (Belk, 1985), have a high entitlement mentality, and their work values are mostly extrinsic. Entitlement has been defined as a “pervasive sense that one deserves more and is entitled to more than others” (Campbell, Bonacci, Shelton, Exline, & Bushman, 2004, p. 31). In the absence of literature that relates to the potential influence of the theory of rising expectations and generational cohort theory on the behaviour of Generation Y in South Africa, this research seeks to: (i) investigate whether Generation Y are indeed materialistic and entitled; (ii) investigate the potential influence of demographic factors on work centrality, work values, materialism, and an entitlement mentality; (iii) investigate the potential influence of work centrality, work values, and materialism on an entitlement mentality; and (iv) investigate the mediating effect of materialism on the relationship between demographic factors, work values, work centrality, and an entitlement mentality in the context of a private college and a public university in South Africa. This research employed a two-stage approach. The first stage, a quantitative study, applied a descriptive approach to validate and justify the research findings that link Generation Y with materialism and entitlement mentality. Entitlement mentality was measured using two dimensions: exploitative and nonexploitative entitlement. Based on a literature review, a model was then developed and tested in the second stage of the study using Structural Equation Modelling. Findings from Stage Two suggested that Generation Y are materialistic and highly entitled, but that their entitlement is non-exploitative. Men were found to be more materialistic than women, but women were found to be more entitled than men. However, both genders were found to have low levels of exploitative entitlement, albeit with men showing slightly higher levels of exploitative entitlement. Gender and age were also significantly associated with materialism and entitlement. However, gender and age were found not to be significantly associated with work centrality. Work centrality was found to be significantly associated with entitlement mentality. Work values, on the other hand, were found not to be significantly associated with entitlement mentality, but were significantly associated with materialism. Materialism was found to be significantly associated with entitlement mentality. On the basis of all of these results, it was concluded that the theory of rising expectations and generational cohort theory might be responsible for the entitlement mentality and materialism, which literature often associates with Generation Y. The results also suggested that for organisations to attract and retain Generation Y employees, managers need to pay attention to extrinsic aspects of the job, such as pay.
Thesis presented for the Degree of Doctor of Philosophy (Business Science, Human Resources Management) in the Faculty of Commerce, Law and Management at the University of the Witwatersrand, Johannesburg, June 2017
Keywords: Entitlement attitudes; Generation Y--Attitudes; College students--Psychology; Higher education--South Africa